Use of Latent autoimmune diabetes in adults clinical risk score in type 2 diabetes - R. Anil Kumar; Surekha B. Shetty; Lalitha R (International Journal of Medical Research and Review, 2017)
Background: Subjects with type 2 diabetes may harbour islet auto antibodies and this has implications on progression of disease and therapeutic options. Clinical tools to distinguish antibody positive individuals are essential to guide the therapy.Objective: To develop a clinical risk score in subjects with Type 2 Diabetes to identify LADA.Methods: We studied 100 persons aged between 25 to 65 years diagnosed as Type 2 Diabetes by FBS>126mg/dl and C-peptide >0.6 ng/ml.Results: 17% of Type 2 Diabetic individuals were GAD positive. 11 were males and 6 were females. GAD positivity in the 25 to 34 years age group was 16.3%, 35 to 44 years age group was 20.8%, 45 to 54 years age group was 21.1%, and in >55 was 0% respectively. GAD positivity with respect to the duration of diabetes 0-5 years, 5-10 years and >10 years was 18.2, 12.3 and 20% respectively. 82.4% of GAD positive type 2 diabetes individuals had BMI <25 kg/m2 and age of onset of diabetes <50 years. Mean BMI, waist circumference and fasting C-peptide were 24.86±4.66, 87.55±10.78 and 2.49±1.41 in GAD negative Type 2 Diabetics. Mean BMI, waist circumference and fasting C-peptide were 21.65±3.46, 80.20±10.03 and 3.04±3.66 in GAD positive Type 2 Diabetics. All 17 GAD positive patients had LADA clinical risk score of 2 or more, So this score should be used in the clinic to suspect LADA patients.Conclusions: LADA clinical risk score is ≥2 in all 17 GAD antibody positive subjects with Type 2 Diabetes. So this scoring system can be used as a tool to suspect LADA patients in the clinical setting. A multicentre study is necessary to further validate this scoring system.